Dynamics in a Delayed Eco-Epidemiological Model with Disease in the Pest (Journal of Nonlinear Modeling and Analysis, 2025)
In ecology, it is of great significance to research the influence ofgestation period on the dynamics of eco-epidemiology. In the paper, we establish and explore a delayed predator-pest model with disease in pest. Wefirst analyze the existence and local stability of each equilibrium of the model.Then, we investigate the existence of Hopf bifurcation at the coexistence equilibrium. Moreover, we calculate the normal form to examine the properties ofHopf bifurcation. Some numerical simulations are conducted to verify the theoretical results obtained and explore how the delay affects the biomass of pest.Our findings may contribute to a better understanding of the mechanisms ofinteraction between species in eco-epidemiology. At the same time, this studyalso provides an insightful perspective into the control of pests in ecosystems.
Keywords: Predator-pest model; eco-epidemiology; gestation delay; Hopf bifurcation; normal form.